Pelestarian Lingkungan Di Desa Semau Kabupaten Tanjung Jabung Barat Provinsi Jambi (Studi Pada Umkm Cantiqe Ecoprint) - Khairatunnisa Akmalia Putri,; Fakhri Usmita, (Sisi Lain Realita, 2024)
Environmental conservation is the process or method of protecting against extinction and destruction. Data from the Regional Environmental Status in Tanjung Jabung Barat Regency shows a continuous decline in mangrove forest area. The subject of this research is the Cantiqe Ecoprint MSME business, located in Semau Village, Tanjung Jabung Barat Regency. The data was obtained through interviews with the Head of Pollution and Environmental Damage Monitoring at the Environmental Agency (DLH), ecoprint business actors, and mangrove charcoal entrepreneurs. Descriptive research collected data based on factors supporting the subject, indicating that the reason for the community's mangrove deforestation is to increase economic income and the limited choices they have to meet their economic needs. Business activities such as those carried out by Cantiqe Ecoprint MSMEs can be used as a new venture for communities that have long relied on activities harmful to the environment. This research shows that the activities of Cantiqe Ecoprint MSMEs have an impact on reducing mangrove deforestation, as the production of ecoprint fabric has become an alternative source of income for communities that previously engaged in mangrove deforestation to increase their earnings. This has now been replaced by the production of ecoprint fabric, which still utilizes mangrove forests but in a way that does not harm the environment.